Osteoplastic Flap Without Obliteration: How I Do It. Issue 5 (September 2018) - Banks, Catherine G.; Garcia, Jaime A. P.; Grayson, Jessica; Yeon Cho, Do; Woodworth, Bradford A.
Background: The osteoplastic flap provides access to pathology of the frontal sinus and is often performed with obliteration, which can result in significant long-term complications. Objective: To describe the authors' approach to osteoplastic flap without obliteration. Methods: Descriptive analysis. Results: Osteoplastic flap without obliteration preserves frontal sinus function while permitting direct access to the frontal sinus. In this study, we demonstrate a combined nonobliterated approach, accessing the frontal sinus with a Draf III approach to remove a large frontal sinus osteoma. Conclusion: The approach provides excellent exposure for large tumors not otherwise accessible via purely endoscopic procedures, permits improved surveillance, and minimizes long-term complications of obliterated sinuses.